The Effect of Preschool Attendance on Secondary School Track Choice in Germany - Evidence from Siblings - Martin Schlotter (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2011)
We study the effect of preschool attendance on secondary school track choice in Germany which is a crucial outcome that largely predicts educational pathways of children. Using data from the German Socio-Economic Panel, multivariate models show a significant positive association between years of preschool attendance and a childs probability of attending the highest school track, that is, German Gymnasium. Including family fixed effects in a sibling model, our estimates become considerablysmaller and are no longer significant, indicating an upward bias in multivariate models. Accounting for several sibling-specific covariates, such as measures of innate abilityand social skills, does not change this result. The low intensity of Germanys centerbased preschool system might be a reason for the zero effects.
Keywords: I20; J13; J24; 330; Preschool education; sibling models; GSOEP; Frühkindliche Bildung; Bildungsniveau; Schulauswahl; Bildungsverhalten; Schätzung; Deutschland